Construction of Nasal Prosthesis for a Patient with Rhino Cerebral Mucormycosis (A clinical Report). - Nadira A Hatim; Munther N Kazanji; Mohammad A Mohi Al-Deen (University of Mosul, College of Dentistry, 2008)
Aim: To construct a nasal prosthesis for a patient with Rhino cerebral mucormycosis disease and ofnear total Rhinectomy. Materials and method: a permanent soft lining material was adapted overframe work of nose made from visible light cure denture base material, then cured, finished andpolished. Results the finished nose was retained by engaging undercut and by the use of eye glass.Conclusion: A custom sculpted prosthesis combined with soft lining material gives a natural texture ofthe nose was accomplished within 24 hour.